Criminal Legal Responsibility For Murder Perpetrators Who Suffer From Severe Mental Disorders (Psychotic) - Muhammad Bayu Pratama; Lidya Rahmadhani Hasibuan; Chairuni Nasution (CV. AFDIFAL MAJU BERKAH, 2024)
Murder is an act that is done intentionally to seize or eliminate the life of another person for which anyone who does it will be held accountable. However, in the Law there is a regulation that a person cannot be held accountable, namely in Article 44 paragraph (1) of the Criminal Code.This research is descriptive with a normative legal writing approach taken from secondary data by processing primary legal materials, secondary legal materials and tertiary legal materials obtained from documentation studies or literature searches or collecting library research data (library research) both offline and online which are then analyzed qualitatively. Based on the research results, it was found that the criteria for perpetrators who experience severe mental disorders in the crime of murder are strange delusions or delusions (the content is clearly unreasonable) and not based on reality, somatic (physical) grandeur, religious, jealousy, hallucinations in any form, then the panel of judges decided that the defendant was guilty of committing the crime of murder, but the defendant could not be punished for the reason of forgiveness in Article 44 paragraph (1) and (2) of the Criminal Code. The criteria for severe mental disorders should be known by the relevant police agency where the defendant works, so that something like this, namely the crime of murder, will never happen so that things like this can be anticipated.